2019
DOI: 10.1111/jce.14233
|View full text |Cite
|
Sign up to set email alerts
|

Stellate ganglion block and cardiac sympathetic denervation in patients with inappropriate sinus tachycardia

Abstract: Background Inappropriate sinus tachycardia (IST) remains a clinical challenge because patients often are highly symptomatic and not responsive to medical therapy. Objective To study the safety and efficacy of stellate ganglion (SG) block and cardiac sympathetic denervation (CSD) in patients with IST. Methods Twelve consecutive patients who had drug‐refractory IST (10 women) were studied. According to a prospectively initiated protocol, five patients underwent an electrophysiologic study before and after SG blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…It was found that after the implementation of SGB in patients with concomitant blood hyperviscosity syndrome, the patients experienced whole blood hyperviscosity and decreased hematocrit, resulting in accelerated blood circulation. 22 SGB also can increase blood flow velocity, blood flow, and vessel diameter in the anterior middle and posterior cerebral arteries and reduce vascular resistance, 23 which is similar to the findings of this study. In fact, the authors have another hypothesis that SGB may also improve hemodynamic indexes by reducing cerebral vascular resistance in patients with low blood pressure or high TCD velocity, and later the authors intend to conduct a detailed study on this point of view by analyzing the cerebral vascular resistance, ipsilateral or contralateral MCA blood flow velocity in patients after ganglion block.…”
Section: Discussionsupporting
confidence: 89%
“…It was found that after the implementation of SGB in patients with concomitant blood hyperviscosity syndrome, the patients experienced whole blood hyperviscosity and decreased hematocrit, resulting in accelerated blood circulation. 22 SGB also can increase blood flow velocity, blood flow, and vessel diameter in the anterior middle and posterior cerebral arteries and reduce vascular resistance, 23 which is similar to the findings of this study. In fact, the authors have another hypothesis that SGB may also improve hemodynamic indexes by reducing cerebral vascular resistance in patients with low blood pressure or high TCD velocity, and later the authors intend to conduct a detailed study on this point of view by analyzing the cerebral vascular resistance, ipsilateral or contralateral MCA blood flow velocity in patients after ganglion block.…”
Section: Discussionsupporting
confidence: 89%
“…Hence, its effects are temporary and reversible. The block can either be achieved as a single injection or through continuous infusion upon placement of a catheter [ 292 , 293 ]. The duration of the block also depends on the half-life of the local anesthetic used, such as bupivacaine or lidocaine.…”
Section: Clinical Parameters Of Autonomic Dysfunction and Evidence Fo...mentioning
confidence: 99%
“…Given that the stellate ganglion synapses with cardiac sympathetic postganglionic fibers [ 4 ], SGB also reduces cardiac sympathetic nervous activity (CSNA). Therefore, SGB has been used as one of the methods for cardiac sympathetic denervation to treat medically refractory arrhythmias driven by enhanced CSNA, such as refractory ventricular arrhythmia, long QT syndrome, and inappropriate sinus tachycardia [ 5 7 ]. Usually, arthroscopic shoulder surgery is performed with patients seated because the sitting position provides excellent intra-articular visualization, reduces intraoperative blood loss, decreases the incidence of traction neuropathy, and facilitates the conversion to an open procedure [ 8 ].…”
Section: Introductionmentioning
confidence: 99%